Bisphenol A and replacements in thermal paper: A review. (September 2017) - Björnsdotter, Maria K.; de Boer, Jacob; Ballesteros-Gómez, Ana
Abstract: Thermal paper contains potentially toxic compounds such as bisphenol A (BPA), which is used as a color developer. BPA has been reported in thermal paper in concentrations up to 42, 600 μg g −1 . The exposure to BPA via dermal transfer has been recently discussed as a significant contribution to the overall human exposure and the estimated daily intake (EDI) has been reported up to 218 μg d −1 . BPA has been also detected in recycled paper with concentrations up to 46 μg g −1 . Due to the fact that BPA is a known endocrine disruptor and migrates from materials, regulatory restrictions have been established to prevent risks for the human health. As a consequence, structural analogues, such as bisphenol S (BPS) have been introduced into the market. Little is known about the presence and toxicity of these emerging replacements, and concern has risen about them. The present review gives an overview of the occurrence and levels of BPA and replacements in thermal paper. BPA is still the most common color developer found in thermal paper, followed by BPS. The analytical methods used for quantification of BPA and BPA replacements in paper products are also reviewed. BPA is transferred from thermal paper products to the finger pads upon handling it. Paper-skin transfer followed by penetration of BPA depends on conditions (e.g. greasiness of fingers and use of hand cream). It is, however, still debated whether thermal paper as a source for human exposure contributes significantly to the overall internal BPA exposure. Graphical abstract: Highlights: BPA is the most common color developer found in thermal paper followed by BPS. Replacements seem to be increasingly introduced on the market. Color developers migrate from thermal paper and can contaminate the environment. Thermal paper seems to be a potential source of exposure of BPA and replacements.